Menggali Peran Ayah: Pengaruh Keterlibatan Paternal dalam Proses Pembelajaran dan Kesejahteraan Psikologis Remaja - Maulida, Rahmadhita; Budiman, Nandang; Muqodass, Idat (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This literature review article exposes the dynamics of the relationship between fathers and adolescents, with a specific focus on the role of paternal involvement in children’s learning process. Drawing upon the framework proposed by Michael E. Lamb (1997), this article delineates the key components of paternal involvement – including engagement, accessibility, and responsibility – and how these dynamics influence adolescents’ academic outcomes, learning motivation, and psychological well-being. This review highlights the importance of an active and constructive paternal presence as a predictor of adolescents’ educational success and socio-emotional adaptation, supported by evidence from recent studies.